Passage of Large Fish Around a Causeway in Prudhoe Bay, Alaska - Craig, P.C.; Griffiths, W.B. (ARCTIC, 1981)
Fish movements around a 2.8 km solid-fill causeway in Prudhoe Bay, Alaska, were examined by tagging anadromous least and arctic cisco (>220 mm) on each side of the causeway in summer and comparing the recapture ratios when the fish were later caught in the Colville Delta commercial fishery 80 km to the west. There was no significant difference in proportions of recaptures among fish (species combined) that did not have to swim around the causeway. Thus available data indicate that the net movements of large least cisco, and probably arctic cisco, were unaffected by this man-made coastal feature.Key words: least cisco, Coregonus sadinella, arctic cisco, Coregonus autumnalis, movements, Beaufort Sea